"Every Life Has Hope”: A Case Study on the Therapeutic Community Approach (TCA) in Drug Rehabilitation (Asia Pacific Journal of Social Innovation, 2022)
Drug addiction makes a person dysfunctional, hence a concern not just for the individual, but also the family and society. This study examines the effectiveness of a drug rehabilitation modality, the Therapeutic Community Approach (TCA), as implemented by “Fazenda de Esperanza”, a private organization in Masbate, Philippines with an aftercare program called the “Living Hope Group”; placing focus on its modality that relies purely on organic detoxification and non-medicated approaches – like value formation as part of a holistic change model. The model gives importance to social bonds or relationships between the drug dependents and their respective families and peers. The crucial role of these relationships is emphasized not only in the recovery process of drug dependents but also in attaining holistic change of the individual.Employing mixed methods in data gathering, through in-depth interviews and focus group discussions, challenges faced by the respondents during rehabilitation and the role of community formed inside the center in overcoming them are explored. Findings reveal that most respondents who finished the program have successfully remained drug-free. All of the respondents affirmed positively the impacts of the two-tiered Therapeutic Community Approach (TCA) – one year in rehabilitation followed by an aftercare program. While the one-year rehabilitation addresses the concern of drug dependency, the latter after care program ensures that the graduates sustain sobriety through strengthened family bonding and a meaningful community support system. Hence this paper recommends the model of modified TCA - using non-medicated approaches and a responsive aftercare program for effective rehabilitation of drug dependents.